Pengaruh Metode Bermain Peran terhadap Literasi Baca Tulis dan Numerasi Anak Usia 5–6 Tahun - R., Erniati; Watini, Sri; Yuliantina, Irma (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study examined the effect of role-playing activities on reading, writing, and numeracy skills in children aged 5-6 years. The study was motivated by low early literacy and numeracy levels in rural areas, as well as the limited number of studies that investigate both skills simultaneously using a factorial experimental design. A quantitative approach was employed using a true experimental factorial 2×2 design involving 32 children aged 5–6 years at Mutiara Kindergarten, Bongkal Malang Village, Kelayang District, Indragiri Hulu Regency, Riau Province. Participants were assigned to an experimental group receiving role-playing activities and a control group using a conventional learning model, with gender considered as a moderating variable. Research instruments included validated assessments of reading and writing literacy and numeracy. Data were analyzed using two-way ANOVA and simple effect tests. The findings revealed significant differences in reading and writing literacy (p < 0.001, η²p = 0.512) and numeracy skills (p < 0.001, η²p = 0.504) between the role-playing and conventional groups. No significant interaction was found between learning model and gender for either literacy or numeracy. Overall, role-playing activities effectively improved literacy and numeracy skills in early childhood and provided empirical evidence through the simultaneous examination of these two abilities within a factorial experimental framework.